Encuentro Internacional sobre la Inspiración - Izquierdo, L.C., Antonio (Alpha Omega, 2019)
Summary: The article describes the content of an International Encounter on the issue of Inspiration, following the exposition of the sis Relations: In what sense does Holy Scripture witness Inspiration? (R. Fabris); Three possible Models of Inspiration (W. Vogels); Inspiration and Canonicity (M. Tábet); The new Methods of Exegesis and the understanding of biblical Inspiration (A.M. Artola); What does Inspiration mean today? A global vision (P. Grech); Biblical Inspiration and “inspiration” of holy Writings of other Religions (A. Amato) Parole chiave: Ispirazione, canone, metodi sincronici, verità, Scritture non cristane Keywords: Inspiration, Canon, Truth, Non Christian Scriptum, Synchronic Methods